Sparkling cyanide - Christie, Agatha, 1890-1976.; Anthony, Nigel (New York, N.Y. : Audio Renaissance : Distributed by Holtzbrinck Publishers, 2001)
In a Luxembourg nightclub, six friends sit down at a table laid for seven. In front of the empty place is a sprig of rosemary, as a remembrance of Rosemary Barton, who was murdered exactly one year earlier-- by one of those present.
Abridged.
In container (18 cm.).
Read by Nigel Anthony.
Keywords: Luxembourg -- Fiction; Mystery fiction